Pupuk Hayati Berbasis Bakteri Endofit - Maria Bintang; Dwi Endah Kusumawati (PROSIDING SEMINAR KIMIA, 2013)
Problem of low agricultural production can be caused by a reduction in agricultural area and the presence of pests and diseases. The use of inorganic fertilizers in the long term can cause negative impacts, so we need new alternative sources of fertilizer that environmentally friendly and effective against pathogens, especially on agricultural crops.Endophytic bacteria as a biocontrol agent should be developed to be biological fertilizers because of some specific strains have been shown to produce antibacterial as well as stimulate plant’s growth. Development of endophytic bacteria as a biological fertilizer would be very beneficial, good for the environment, farmers and industry.